Homebird - Blacker, Terence (New York : Bradbury Press, 1993)
Thirteen-year-old Nicky Morrison runs away from boarding school and problems at home to the tough life on the streets of London.
"First published 1991 by Piccadilly Press, London"--T.p. verso.
Booklist.
Publisher's Weekly.
School Library Journal.
Young Adult
Keywords: Family problems -- Fiction; Runaways -- Fiction; Family problems -- Fiction; Runaway teenagers -- Fiction; London (England) -- Fiction; London (England) -- Fiction